Luxury Uptake and Removal of Phosphorus from Water Column by Representative Aquatic Plants and Its Implication for Wetland Management. (12th February 2012) - Shardendu, Shardendu; Sayantan, D.; Sharma, Deepti; Irfan, Sufia
Abstract : Aquatic plants with their high relative growth rates efficiently absorb nutrients from their surrounding media, thereby providing a simple and inexpensive solution for nutrient-polluted aquifers. The present study determined the P accumulation efficiencies of four different aquatic plants namely, Eleocharis plantaginea, Eichhornia crassipes, Pistia stratiotes, and Hydrilla verticillata from the 6043 ha Kabar Wetland (86°05′ E to 86°09′ E, 25°30′ N to 25°32′ N). The aim of the study was to select the most efficient P accumulator. Water, sediment, and plant samples from Kabar were monthly analyzed for P content for 13 months from July 2009 to July 2010. Pistia stratiotes L. accumulated the highest amount of tissue P (1.06 ± 0.22 mg/g dw). The maximum capacity of luxury uptake of P under greenhouse conditions as exhibited by Pistia was further tested. Pistia individuals tolerated up to 50 mg/L phosphate medium and accumulated6.12 ± 0.95 mg/g dw P after 35 days under greenhouse conditions. Up to 91% phosphate was removed from the surrounding medium within 60 days at 50 mg/L supply. Tissue P levels increased with increasing phosphate levels in the surrounding media but variation with incubation period was statistically insignificant. Our studies present Pistia as more efficient than other common wetland species like Eichhornia, Phragmites, Typha, and so forth when grown in the sub-tropics and confirm its ability to ameliorate P-polluted subtropical wetlands.